ISU DAN PERMASALAHAN PRODUK HALAL DI LINGKUNGAN SEKOLAH - Miladanta, Algi Nurahman; Nuryantini, Ade Yeti; Windayani, Neneng (Investama : Jurnal Ekonomi dan Bisnis, 2024)
This article discusses issues and problems related to halal products in the school environment, with a focus on the integration of halal products, student awareness, and accessibility of halal products. In the context of school education, the main challenges include the need for a holistic approach in providing halal products, clear policies regarding halal products, and a deep understanding of the concept of halal products. Adequate availability and accessibility of halal products in the school environment is also an important focus in creating an inclusive school environment for Muslim students. With a holistic understanding and increased awareness, it is hoped that the school environment can support students' religious needs more effectively. This research methodology is based on systematic literature analysis from leading sources, which is then synthesized to present a comprehensive picture of the issue of halal products in schools. Thus, this article provides comprehensive insight into halal product issues in the school education environment.